1997
DOI: 10.1038/nm0897-860
|View full text |Cite
|
Sign up to set email alerts
|

Association of simian immunodeficiency virus Nef with cellular serine/threonine kinases is dispensable for the development of AIDS in rhesus macaques

Abstract: The nef gene of simian immunodeficiency virus (SIV) is essential for high viral load and induction of AIDS in rhesus monkeys. A mutant form of the SIVmac239 Nef, which contains changes in a putative SH3-binding domain (amino acids 104 and 107 have been changed from PxxP to AxxA), does not associate with cellular serine/threonine kinases, but is fully active in CD4 downregulation and associates with the cellular tyrosine kinase Src. Infection of two rhesus macaques with SIVmac239 containing the mutant AxxA-Nef … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 39 publications
11
127
1
Order By: Relevance
“…Of interest, the SIV Nef WTQ mutant appears to co-precipitate more efficiently with fulllength Hck than HIV-1 Nef in vivo, suggesting some additional mechanisms of binding such as through its SH2 domain. Indeed, although a strong selective pressure was noted in vivo to restore an experimentally disrupted proline motif in SIV Nef (11), this motif appears dispensable for Src binding in intact cells (10). This is in strike contrast to HIV-Nef binding to Hck which requires an intact proline motif (30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest, the SIV Nef WTQ mutant appears to co-precipitate more efficiently with fulllength Hck than HIV-1 Nef in vivo, suggesting some additional mechanisms of binding such as through its SH2 domain. Indeed, although a strong selective pressure was noted in vivo to restore an experimentally disrupted proline motif in SIV Nef (11), this motif appears dispensable for Src binding in intact cells (10). This is in strike contrast to HIV-Nef binding to Hck which requires an intact proline motif (30).…”
Section: Resultsmentioning
confidence: 99%
“…Elucidation of incongruences in functional aspects between SIV and HIV-1 Nef molecules is indispensable for the use of SIV Nef as a model for drug design. As an alternative to mutational analysis in the proline motif (4,10,11,26), we now propose to design mutations that selectively inactivate specific Nef functions to assess their effect on viral replication and pathogenesis in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospho-amino acids analysis demonstrated that the majority of the phosphorylation of the p62/p95/p85 species occurred on serine residues (Fig. 1C), indicating that murine NAK, like its human and simian homologues (47,48,56,59,64,65,74), is a serine-threonine kinase. These results indicated that Nef binds to a murine serine kinase in primary immune cells of Tg mice.…”
Section: Nak Activity Is Present In Thymocytes Macrophages and Dcs mentioning
confidence: 94%
“…Observations from naturally HIV-1-infected individuals indicated that Nef functions on downmodulation of CD4 and MHC-I could be related to the pathogenesis of AIDS (Carl et al, 2001;Tobiume et al, 2002), however the real contribution of these functions still needs to be demonstrated (Crotti et al, 2006). The motifs in Nef that mediate CD4 downregulation were considered critical for SIVmac replication in rhesus macaques, however MHC-I downregulation by Nef is not sufficient for optimal virulence of SIVmac early in infection Lang et al, 1997;Schindler et al, 2004). Moreover, the solely importance of the CD4 downmodulation for SIVmac pathogenesis in experimental models has been challenged (Jesus da Costa et al, 2009).…”
Section: Downmodulation Of Cd4 and Mhc-imentioning
confidence: 99%